IUTAM Symposium on Dynamics Modeling and Interaction Control in Virtual and Real Environments Proceedings of the IUTAM Symposium on Dynamics Modeling and Interaction Control in Virtual and Real Environments, held in Budapest, Hungary, June 7-11, 2010 - IUTAM Symposium on Dynamics Modeling and Interaction Control in Virtual and Real Environments (2010 Budapest, Hungary); Stépán, Gábor 1953-.; Kovács, László L.; Tóth, András; SpringerLink (Online service). (Dordrech Springer Netherlands, 2011)
This volume contains the invited paper as presented at the IUTAM Symposium on Multibody Dynamics and Interaction Control in Virtual and Real Environments held in Budapest, Hungary, June 7?11 2010. The symposium aimed to bring together specialists in the fields of multibody system modeling, contact/collision mechanics and control of mechanical systems. The offered topics included modeling aspects, mechanical and mathematical models, the question of neglections and simplifications, reduction of large systems, interaction with environment like air, water and obstacles, contact of all types, control concepts, control stability and optimization. Discussions between experts in these fields made it possible to exchange ideas about the recent advances in multibody system modeling and interaction control, as well as about the possible future trends. The presentations of recent scientific results may facilitate the interaction between scientific areas like system/control engineering and mechanical engineering. Papers on dynamics modeling and interaction control were selected to cover the main areas: mathematical modeling, dynamic analysis, friction modeling, solid and thermomechanical aspects, and applications. A significant outcome of the meeting was the opening towards applications that are of key importance to the future of nonlinear dynamics.
Dynamics modeling and control of robots:The ACROBOTER Platform ? Part 1: Conceptual Design and Dynamics Modeling Aspects, by László L. Kovács, Ambrus Zelei, László Bencsik and Gábor Stépán -- The ACROBOTER Platform - Part 2: Servo-Constraints in Computed Torque Control, by Ambrus Zelei and Gábor Stépán -- The 3D-Pendulum at theWorld Exhibition 2010 - Control Design and Experimental Results, by Thomas Gorius, Robert Seifried and Peter Eberhard -- Contact to Sample Surface by Self-Excited Micro-Cantilever Probe in AFM, by H. Yabuno, M. Kuroda, T. Someya -- DYNAMICS AND TRAJECTORY PLANNING OF A SPACE ROBOT WITH CONTROL OF THE BASE ATTITUDE, by Fumiya Matsumoto and Hiroaki Yoshimura -- Applications and control of bio-inspired robots: Optimal Control of a Two-Link System Moving in a Fluid, by Felix L. Chernousko -- Straight Worms Under Adaptive Control And Friction - Part 1: Modeling, by Carsten Behn and Klaus Zimmermann -- Straight Worms Under Adaptive Control And Friction - Part 2: Adaptive Control, by Carsten Behn and Klaus Zimmermann -- Current Sensing in a Six-Legged Robot, by Q. Bombled and O. Verlinden -- Vehicle dynamics and control: Resonances of Road-Vehicle Systems with Nonlinear Wheel Suspensions, by Walter V. Wedig -- Real-Time Vehicle Dynamics using Equation-Based Reduction Techniques, by Lars Mikelsons, Thorsten Brandt and Dieter Schramm -- Mathematical modeling of oscillatory systems: Solution and stability of a linear fractionally damped oscillator, by Z H Wang -- THE FRACTIONAL DERIVATIVE AS A COMPLEX EIGENVALUE PROBLEM, by Masaharu Kuroda -- Discontinuity-Induced Bifurcations due to Saturations, by Gustavo A. Osorio, Fabiola Angulo and Gerard Olivar -- Bifurcations in Hysteresis Systems due toVibrations and Impacts, by Fabio A. Leyton, Jorge E. Hurtado and Gerard Olivar -- Complex Nonlinear Response of a Piecewise Linear Oscillator: Experiment and Simulation, by James Ing, Ekaterina Pavlovskaia and Marian Wiercigroch -- Optimization of a vibrating screen?s mechanical parameters, by Bela Csizmadia, Attila Hegedus, Istvan Keppler -- Biomechanics and rehabilitation -- Internal lever arm model for myosin II, by Andras Bibo, Mihaly Kovacs, and Gyorgy Karolyi -- Nonlinear wave propagation in the cochlea with feed-forward and feed-backward, by Walter Lacarbonara and Charles R. Steele --  Sensitivity investigation of three-cylinder model of human knee joint, by I. Bíró, B. M. Csizmadia, G. Krakovits3, A. Véha -- On the performance index optimization of a rheological dynamical system via numerical active control, by Pawe? Olejnik and Jan Awrejcewicz -- Characterization of a least effort user-centered trajectory for sit-to-stand assistance, by V. Pasqui, L. Saint-Bauzel and O. Sigaud -- Micro-electromechanical Systems -- Multibody system model of MEMS resonator, by Ákos Miklós and Zsolt Szabó -- Control of elastic wave propagation in piezoceramic cylinders of sector cross section, by Puzyrev Vladimir, Storozhev Valeriy -- SHM of Composite Cylindrical Multilayered Shells with Delaminations, by A. Muc -- Optimal Design of Eigenfrequencies for Composite Structures Having Piezoelectric Sensors or Actuators, by A. Muc, P. K?dziora -- Vibration control of defects in carbon nanotubes, by A. Muc, M. Chwa? -- Influence of Noise on Discrete Breathers in Nonlinearly Coupled Micro-Oscillator Arrays, by Subramanian Ramakrishnan and Balakumar Balachandran -- Modeling dry friction -- New Models of Friction and Their Applications in Rigid Body Dynamics, by A.V. Karapetyan -- DIFFERENT MODELS OF FRICTION IN DOUBLE-SPHERICAL TIPPE-TOPDYNAMICS, by A. A. Zobova -- Frictional Vibration of a Cleaning Blade in Laser Printers, by G.Kono, Y.Inagaki, T.Nohara, M.Kasama, T.Sugiura, H.Yabuno -- Thermoelasticity aspects -- Refinements of Classical Beam Theory for Beams with a Large Aspect Ratio of Their Cross-Sections, by J. P. Meijaard -- Dynamic contact problems for shells with moderately large deflections, by Igor Bock -- Application of Steepest Descent Path Method to Lamb?s Solutions for Scattering in Thermoelastic Half-plane, by Po-Jen Shih, Sheng-Ping Peng, Chau-Shioung Yeh, Tsung-Jen Teng3, Wen-Shinn Shyu.
Electronic reproduction .
Keywords: Electronic books; Dynamics -- Congresses; Virtual reality -- Congresses